The prognostic value of biventricular long axis strain using standard cardiovascular magnetic resonance imaging in patients with hypertrophic cardiomyopathy. (1st November 2019) - Yang, Fuyao; Wang, Jie; Li, Yuancheng; Li, Weihao; Xu, Yuanwei; Wan, Ke; Sun, Jiayu; Han, Yuchi; Chen, Yucheng
Abstract: Background: Long axis strain (LAS) is a parameter derived from standard cardiovascular magnetic resonance imaging. However, the prognostic value of biventricular LAS in hypertrophic cardiomyopathy (HCM) is unknown. Methods: Patients with HCM (n = 384) and healthy volunteers (n = 150) were included in the study. Left ventricular (LV)-LAS was defined as the percentage change in the length measured from the epicardial border of the LV apex to the midpoint of a line connecting the mitral annulus at end-systole and end-diastole. Right ventricular (RV)-LAS represented the percentage change of length between epicardial border of the LV apex to the midpoint of a line connecting the tricuspid annulus at end-systole and end-diastole. The primary endpoint was a combination of all-cause death and sudden cardiac death aborted by appropriate implantable cardioverter-defibrillator discharge and cardiopulmonary resuscitation after syncope. The secondary endpoint was a combination of the primary endpoint and hospitalization for congestive heart failure. Results: Twenty-nine patients (7.6%) achieved the primary endpoint, and the secondary endpoint occurred in 66 (17.2%) patients. In multivariate Cox regression analysis, RV-LAS was an independent prognostic factor for the primary (hazard ratio (HR), 1.13) and secondary (HR, 1.11) endpoints. In the subgroup of patients with a normal RV ejection fraction (EF) (>45.0%, n = 345), impaired RV-LAS was associated with adverse outcomes and might add incremental prognostic value to RVEF and tricuspid annular plane systolic excursion (TAPSE) ( p < 0.01). Conclusions: RV-LAS is an independent predictor of adverse prognosis in HCM in addition to RVEF and TAPSE. Highlights: Long axis strain is a new parameter that is easily derived from CMR imaging. RV-long axis strain is an independent prognostic factor in HCM. RV-long axis strain may provide incremental value beyond RVEF in HCM.